2013
DOI: 10.1021/ef3018089
|View full text |Cite
|
Sign up to set email alerts
|

Application of Wada’s Group Contribution Method to the Prediction of the Speed of Sound of Biodiesel

Abstract: Biofuels are an important alternative to environmental sustainability, and biodiesel has a detached contribution to this scenario. The increasing use of biodiesel requires the knowledge of several thermophysical properties of this biofuel. This work addresses the measurements of the speed of sound and density at atmospheric pressure of five fatty acid methyl esters (methyl caprylate, methyl caprate, methyl palmitate, methyl stearate, and methyl linoleate). These data are used to test Wada's group contribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 18 publications
(73 reference statements)
1
29
1
Order By: Relevance
“…Moreover, since the FAMEs present a higher value for density than the corresponding FAEEs with the same number of carbon atoms in acid moiety, as already shown in Pratas et al [9] the magnitude of the densities for ethylic biodiesels is expected to be lower than that of the corresponding methylic biodiesels. Regarding the speed of sound, as previously observed for methylic biodiesels [13], a difference in the speed of sound of only ca. 1.0% is observed between the four types of biodiesels studied.…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…Moreover, since the FAMEs present a higher value for density than the corresponding FAEEs with the same number of carbon atoms in acid moiety, as already shown in Pratas et al [9] the magnitude of the densities for ethylic biodiesels is expected to be lower than that of the corresponding methylic biodiesels. Regarding the speed of sound, as previously observed for methylic biodiesels [13], a difference in the speed of sound of only ca. 1.0% is observed between the four types of biodiesels studied.…”
Section: Resultssupporting
confidence: 79%
“…In a previous work, we showed that this model could provide a good prediction of the speed of sound of methyl esters and the corresponding methylic biodiesels [13]. This model simply relates speed of sound (u in m s À1 ) with density (q in kg m À3 ), molecular mass (M w in g mol À1 ) and molecular compressibility (j m ) according to the following equation:…”
Section: Prediction Of Speed Of Soundmentioning
confidence: 99%
See 3 more Smart Citations